An Efficient Oxygen Evolution Catalyst for Hybrid Lithium Air Batteries: Almond Stick Type Composite of Perovskite and Cobalt Oxide. Issue 9 (1st January 2016) - Gwon, Ohhun; Kim, Changmin; Kwon, Ohhun; Jeong, Hu Young; Park, Heai-Ku; Shin, Jeeyoung; Ju, Young-Wan; Kim, Guntae
Abstract : We investigated the electrochemical composite effect between cobalt oxide and Nd0.5 Sr0.5 CoO3- δ (Co-NSC). A double phase Co-NSC composite was successfully synthesized by a new synthesis process rather than a single phase Nd0.5 Sr0.5 Co1.1 O3- δ perovskite. The composite has good catalytic activity, high number of transferred electrons (3.9) compatible with Pt/C, and low concentration of the peroxide species (HO − 2 ) yields (<5%). Also, it shows the outperformed onset potential (0.576 V vs. Hg/HgO) of the oxygen evolution reaction (OER) at −2.0 mA cm −2, indicating higher current density than perovskite related catalysts such as Ba0.5 Sr0.5 Co0.8 Fe0.2 O3- δ (BSCF), La1.7 Sr0.3 NiO4 (LSN), LaNiO3 (LNO) and the state-of-the-art rutile IrO2 . The good catalytic activity of Co-NSC is ascribed to the higher amount of Co 3+ cations and higher Oad /Olattice ratio. Interestingly, the cyclic performance of the composite is also remarkably stable without observable degradation in a hybrid lithium air cell.